Volcanismo freatomagmático monogenético máfico relacionado con salares: dos casos de estudio de la Puna, Argentina - Orellana, Daiana (2025)
Mafic monogenetic volcanoes and salt pans or salars are ubiquitous in the Puna plateau of the Central Andes. In this contribution, we present the study of two Pleistocene mafic monogenetic centers, the Panqueque center emplaced on the western margin of the Salar de Arizaro and the Medialuna center emplaced within the same salar. Both centers had initial explosive phreatomagmatic activity that progressed to explosive magmatic (Strombolian) activity and ended with effusive activity. However, differences in magma flux, bedrock composition, and magma-water interaction resulted in deposits with different volumes and characteristics and, consequently, varied landforms. The magma batch that formed the Panqueque center (0.098 km3) passed through a heterogeneous bedrock marked by the transition between clastic and evaporitic deposits. Variable magma-water interaction generated two stages of phreatomagmatic activity, producing first a tuff ring or rings and then tuff cones, followed by Strombolian activity. Activity culminated with two phases of volumetrically dominant lava flows. In contrast, the much smaller Medialuna center (0.00016 km3) was formed by a magma batch that ascended through the mostly homogeneous halite-rich core of the salar. The magma interacted with water-saturated evaporitic sediments and fragmented close to the surface, generating a small asymmetric tuff ring. A minor final stage of magmatic activity consisted of ballistic fall activity and a lava cap at the conduit. The Panqueque center pyroclastic deposits do not show any specific feature that alludes to the salar environment, possibly because they formed at the salar margin where alluvial clastic sediments are abundant. Conversely, the Medialuna center deposits do have a few features, namely the lack of lithics, the possible total disintegration of the mechanically weak and friable evaporites into fine to very fine ash particles, and the presence of aggregates cemented by gypsum/salts that may be diagnostic of salar-related phreatomagmatic activity.